Strategic Performance Management: A Case Study of Company A’s Response to the Competitive Environment - Zhongling, Wang; Ruanggoon, Jirapong; Farungthong, Sittichai (Science, Technology, and Social Sciences Procedia, 2024)
The purpose of this study was to: 1) Analyze the current status and identify existing problems in Company A’s performance management; 2) Formulate performance management strategies for Company A; and 3) Provide guidelines for Company A to implement the performance management strategies in the competitive market environment. This study adopted mixed methods research. Quantitative data were collected through a questionnaire survey, with 400 respondents selected through simple random sampling. Data were analyzed using frequency and percentages. Qualitative data were collected through document study, examining internal documents related to the performance management system and various performance metrics within the company, and through in-depth interviews with 4 senior managers and 26 mid-level employees, totaling 30 individuals. Data analysis was conducted using content analysis and thematic analysis, with data triangulation employed to ensure validity. The findings revealed that: 1) Company A faced complex challenges in performance management due to technological advancements, organizational dynamics, and leadership requirements. The shift towards digital performance management necessitated more efficient and flexible systems, while effective leadership was crucial for clear communication, team management, and employee engagement. Company A encountered several problems in its performance management efforts, including insufficient integration of strategic objectives, communication barriers, and misaligned incentives. Furthermore, balancing short-term gains with long-term strategic planning remained a significant challenge; 2) The performance management strategies of Company A focused on enhancing corporate culture, aligning strategic objectives with performance goals, and utilizing data-driven approaches; and 3) The guideline for Company A to implement performance management strategies in the competitive market environment involved aligning performance with organizational goals through a goal cascade process, empowering managers with tailored training, leveraging technology for data-driven insights, fostering a culture of continuous improvement, and enhancing communication channels for transparent feedback.